Model‐based fault accommodation control of multiagent systems. Issue 2 (3rd January 2020) - Huang, Sunan; Lin, Feng
Abstract: In recent years, consensus problem in multiagent systems (MASs) has been studied extensively. However, when a fault occurs in a MAS, this problem becomes more challenging. In this paper, we present several fault accommodation control schemes for a class of MASs. First, actuator faults are considered in our MASs. Second, a fault detection is proposed, which is constructed based on a residual and threshold value. Third, both passive and active fault accommodation control schemes are presented. Finally, a simulation example is given to show the effectiveness of the proposed control method. Abstract : Model‐based fault detection approach for a class of multi‐agent systems. Model‐based passive fault accommodation control for a class of multi‐agent systems. Model‐based active fault accommodation control for a class of multi‐agent systems.